Dietary intake and occupational status among female youths of Thai Nguyen, Vietnam - Tran, Lan Mai; Nguyen, Phuong Hong; Hoang, Nga Thu; Truong, Duong Thuy Thi; Tran, Trang Huyen Thi; Bui, Diep Ngoc; Hoa, Hanh Thi Hong; Hua, Diem Thi; Bergeron, Gilles (New York Academy of Sciences, 2023)
Adolescence is a sensitive transition time that affects rights, roles, and responsibilities in food choice, yet limited evidence exists on dietary intakes during this critical period. This study assessed the food consumption pattern and the adequacy of energy, macronutrient, and micronutrient intakes among female youth belonging to three occupational groups in Vietnam. Dietary intakes were measured for 1001 participants aged 16–22 years using INDDEX24's 24-h recall method. Multivariate regression analyses were conducted to examine differences in diet outcomes among the three occupational groups. Dietary diversity was similar across groups but workers, compared to high school and college students, consumed less baked/grain-based sweets and fast foods, and more soft drinks, other sweets, and processed meat. Two-thirds of the sample showed energy intake lower than the estimated energy requirement, while a substantial percentage had insufficient or excessive intake of carbohydrate and fat. The mean probability of adequacy of nutrient intakes was low (0.33) and not different across all three occupational groups except for folate, which favored workers. Our study provides novel evidence supporting the development and implementation of interventions to achieve national targets, with emphasis on female youths who undergo special transitions in education, occupation, and lifestyle.